Transformation of Islamic Economics: Opening Halal Opportunities Amid the Dynamics of Society 5.0 - Umdah Aulia Rohmah; Mu’adil Faizin; Muhammad Arfianto Pandu W. (el-Jizya : Jurnal Ekonomi Islam, 2024)
Various correlated variables affect the transformation of the Islamic economics in the context of society 5.0. These variables include halal supervision and certification, public awareness of sharia principles, product and service innovation, collaboration between Islamic financial institutions and technology companies, and integration of advanced technology. New product and service innovations, such as sukuk bonds and Islamic mutual funds, also contribute greatly to the transformation of the Islamic economics. On the other hand, the integration of technologies such as fintech and blockchain has increased accessibility and transparency in Islamic financial services, and increased public awareness of the benefits of the Islamic economics has increased demand for Islamic goods and services. Technology companies and Islamic financial institutions work together to produce innovations in Islamic financial services, while technologies such as blockchain ensure authenticity and transparency in the halal industry. Understanding these components is important in transforming the Islamic economics towards a more inclusive, sustainable and ethical economic system in a 5.0 society.